Nitrate detoxification using antioxidants and probiotics in the water for rabbits - Attia, Youssef A.; El Hamid E., Abd; Ismaiel, Ahmad M.; de Oliveira, Maria C.; Al-Harthi, Mohammed A.; El-Naggar, Asmaa S.; Simon, Gustavo A. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Agricultural practices increase groundwater pollution from nitrate. High nitrate intake could negatively affect animal growth. Objective: To determine the effects of different levels of nitrate in drinking water on digestive, liver, and kidney functions, and on water and feed intake, and to determine the ability of vitamin C, vitamin E + selenium (Se) or probiotics to overcome the effects of nitrate in New Zealand White rabbit bucks. Methods: Forty-two male rabbits were randomly distributed into six treatment groups: 1) control group (with no nitrate); 2) 350 ppm nitrate; 3) 700 ppm nitrate; 4) 700 ppm + 200 ppm vitamin C; 5) 700 ppm + 200 ppm vitamin E + Se; and 6) 700 ppm + 1000 ppm probiotic. Productive performance, digestive, liver, and kidney functions, and hepatic and renal histology were evaluated. Results: Water intake was reduced (p<0.05) by the 350 ppm nitrate treatment. Rabbits given 700 ppm nitrate showed lower (p<0.05) dry matter intake, nutrient digestibility, and increased (p<0.05) water and nitrate intake, as well as urea concentration, and aspartate aminotransaminase (AST) and alanine aminotransferase (ALT) activity. Vitamin C, vitamin E + Se and probiotics improved (p<0.05) feed intake and nutrient digestibility, and reduced (p<0.05) water and nitrate intake, urea concentration, and AST and ALT activities. Conclusion: Rabbits may tolerate up to 350 ppm of nitrate, but 700 ppm of nitrate negatively affect digestive, liver, and kidney functions, which are improved by vitamin C, vitamin E + Se and probiotic supplementation.